Degradation of polymeric bellows effecting life cycle of constant-velocity joint. Issue 1 (2nd January 2018) - Binar, Tomáš; Švarc, Jiří; Bálková, Radka; Mikulíková, Regina; Dostál, Petr
ABSTRACT: One broken and three new polymeric constant-velocity boots (bellows) being a spare part of a constant-velocity joint in two military vehicles were analyzed to identify basic composition and to determine if composition or structure of broken bellows differ. Infrared spectroscopy, differential scanning calorimetry, and thermogravimetry were used for analyses. Bellows for both vehicles are produced from thermoplastic elastomer. Broken bellows is chemically degraded and material just from the fracture is deformed plastically. The life cycle of bellows depends especially on applied stress and temperature (that about −20°C seems to be critical due to crystallization of soft segments).